2021
DOI: 10.1002/cncr.33496
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Patient‐Reported Outcomes Measurement Information System to assess quality of life among patients with breast cancer initiating care at an academic center

Abstract: Background Symptom burden and reduced quality of life (QOL) are considerable hurdles in oncology. The authors used the Patient‐Reported Outcomes Measurement Information System (PROMIS), which assesses physical and psychosocial health, to establish a mean symptom burden, examine potential drivers, and characterize severe symptom burden in breast cancer patient subgroups with the goal of characterizing stage IV patient QOL and triaging patients to individualized supportive care services. Methods New patients at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
3
5
0
Order By: Relevance
“…In this study, we reported data on the subjective and objective measures of physical function among Hispanic women with breast cancer. We found that some measures of physical function such as TUG and 4SB were worse in Hispanics, while PROMIS-PF score, PROMIS-F score, STS, and GS were comparable to women of other race/ethnicity with breast cancer, as reported in the literature (Blackwood & Rybicki, 2021a, 2021bMatthys et al, 2021;Van der Weijden-Van Doornik et al, 2017). In addition, we also found that one in every five patients in our sample had depression.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, we reported data on the subjective and objective measures of physical function among Hispanic women with breast cancer. We found that some measures of physical function such as TUG and 4SB were worse in Hispanics, while PROMIS-PF score, PROMIS-F score, STS, and GS were comparable to women of other race/ethnicity with breast cancer, as reported in the literature (Blackwood & Rybicki, 2021a, 2021bMatthys et al, 2021;Van der Weijden-Van Doornik et al, 2017). In addition, we also found that one in every five patients in our sample had depression.…”
Section: Discussionsupporting
confidence: 86%
“…For example, in a study done by Matthys et al (2021), breast cancer survivors showed that PROMIS-PF and PROMIS-F scores were comparable to that of our patient population. Similar results were reported in a study among 2,968 cancer patients, which also showed similar results to ours (Jensen et al, 2017).…”
Section: Subjective Physical Function Measuressupporting
confidence: 71%
“…If shown to be concurrently valid, PROMIS may adequately replace PROMs and reduce both patient and physician burden. Previous studies have found that PROMIS sufficiently captures information obtained through disease-specific PROMs 4,5,14–16 . PROMIS is unique in that it utilizes an iterative CAT system, based on item response theory that improves flexibility, sensitivity, and efficiency 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, nomograms were constructed to predict the prognosis of stage IV BC patients after 3 or 5 years, which may be used as a reference for clinicians to decide whether to perform surgery in these patients. However, for older patients with metastatic tumors, the survival prognosis may not be the key to their well-being compared with other endpoints, such as functional status, quality of life and complications with standard therapy options [24,25]. Unfortunately, no relevant data were recorded in the SEER database.…”
Section: Discussionmentioning
confidence: 99%